A salicylate-functionalized PET packaging to counteract blue discoloration on mozzarella cheese under cold storage. (June 2022) - Caputo, Leonardo; Quintieri, Laura; Bugatti, Valeria; Gorrasi, Giuliana
Abstract: In this work we tested a new technological solution to extend the shelf-life of Mozzarella cheese using a salicylate-functionalized PET packaging. To this aim, we inoculated ready-to-sell Mozzarella cheeses with Pseudomonas lactis ITEM 17298 strain, responsible for blue discoloration; mozzarella cheeses packed in treated or untreated trays were stored at 4 °C and monitored up to blue discoloration occurred. Results from microbiological analyses showed inhibitory effect against the pigmenting strain up to 8 days of cold storage in Mozzarella cheese packed in treated trays compared to the control samples. Likewise, CIELab values of b* and hue did not differ from those found on the uninoculated Mozzarella cheeses, delaying the appearance of bluish spots by approximately 2 days. Furthermore, the use of treated trays unpaired the formation of the biofilm by significantly reducing the amount deposited inside the treated trays compared to the control ones. For the first time, therefore, the use of an antimicrobial packaging with high technology readiness level has delayed the blue mozzarella occurrence specially contaminated samples. Further trials will have to be undertaken to optimize the salicylate concentration released in the tray in order to abate the risk of this fresh dairy product withdrawal from the market. Highlights: Salicylate activated coated was used to functionalise PET trays. Active trays reduced blue pigmenting P. lactis ITEM 17298 load during cold storage. Active trays blue discoloration inhibited blue discoloration up to 8 days of storage. Biofilm biomass on tray surface was inhibited by 50% throughout cold storage. Salicylate-functionalized packaging is promising to counteract pseudomonads spoilage.